2010
DOI: 10.1080/00150193.2010.482005
|View full text |Cite
|
Sign up to set email alerts
|

Structure Control of NaNbO3Template for Textured Ceramics Synthesized by Two-Step Molten Salt Method

Abstract: In this paper, through control the precursor's structure with layer morphology, the platelike particles with different edge length and thickness can be syntheszed by the two step molten salt (MSS) method. The results of SEM showed that the NaNbO 3 particles were characterized by platelet-like morphology with an edge length of 10∼20 µm and a thickness of 1∼4 µm. The results of XRD indicated the NaNbO 3 particles synthesized had a strong orientation in {0 0 l} crystal planes. The plate-like NaNbO 3 particles we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[1][2][3]9,10,14,15,17) Two-step molten salt synthesis has been conventionally utilized for fabricating plate-like NN particles. [1][2][3]9,10,14,15,17,28) In this method, Bi 2:5 Na xÀ1:5 Nb x O 3xþ3 (x ¼ 2{8) particles having a plate-like shape are presynthesized as the precursor at a temperature higher than 1100 C. 10,17,28) Using a topochemical microcrystal conversion method, plate-like NN particles are subsequently synthesized from the mixture of the precursor and NaCl at 1000 C. 10,17,28) The twice heat-treating processes and washing treatment to remove a by-product of Bi 2 O 3 with an acid solution are required to prepare the plate-like NN particles. 28) In addition, since the plate-like NN particles are polycrystalline, the plate surfaces are rugged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]9,10,14,15,17) Two-step molten salt synthesis has been conventionally utilized for fabricating plate-like NN particles. [1][2][3]9,10,14,15,17,28) In this method, Bi 2:5 Na xÀ1:5 Nb x O 3xþ3 (x ¼ 2{8) particles having a plate-like shape are presynthesized as the precursor at a temperature higher than 1100 C. 10,17,28) Using a topochemical microcrystal conversion method, plate-like NN particles are subsequently synthesized from the mixture of the precursor and NaCl at 1000 C. 10,17,28) The twice heat-treating processes and washing treatment to remove a by-product of Bi 2 O 3 with an acid solution are required to prepare the plate-like NN particles. 28) In addition, since the plate-like NN particles are polycrystalline, the plate surfaces are rugged.…”
Section: Introductionmentioning
confidence: 99%
“…28) In addition, since the plate-like NN particles are polycrystalline, the plate surfaces are rugged. 9,14,17,28) The driving force of the template orientation is a sharing force applied to templates during slurry flow. The rugged plate surfaces, which interfere with the smooth slurry flow, are undesirable for the templates.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the anisotropic particles have recently found use in a sophisticated processing technology such as a templated grain growth method for synthesizing textured ceramics. [26,27] …”
Section: Full Papermentioning
confidence: 98%
“…Compared with the lead-based ceramics, however K 0.5 Na 0.5 NbO 3 (KNN) ceramics still show poor piezoelectric properties, restricting its applications in industry [10][11][12][13][14]. It is reported that the piezoelectric properties of KNN can be enhanced significantly through texturing by reactive-templated grain growth (RTGG) method [15,16]. In this method, the synthesis of plate-like NaNbO 3 (NN) template particles is of a key step to obtain the grain-oriented KNN ceramics.…”
Section: Introductionmentioning
confidence: 98%